A case study of flood frequency analysis by intercomparison of graphical linear log-regression method and Gumbel's analytical method in the Vaigai river basin of Tamil Nadu, India. (January 2022) - Ramasamy, M.; Nagan, S.; Senthil Kumar, P.
Abstract: Flood Frequency Analysis (FFA) is a systematic tool used for an efficient hydraulic structures design, operation and maintenance. An effort is made to study and compare the Linear Log Regression Graphical Method (LLRGM) and Gumbel's Analytical Method (GAM) to assess the future flood magnitude for any given Return Period (RP). Twenty-four years of annual daily peak flood flow value recorded at Vaigai reservoir gauging station between the year 1995 and 2018 was used in the two methods for detailed analysis. The results indicated that the GAM predicts the maximum possible optimum future flood in comparison with the LLRGM. This conclusion was drawn based on the coefficient of determination R 2 obtained as 0.8904, which is nearing 1. Based on the analytical method of Gumbel's, the magnitude of frequency factor K has been introduced based on the size of data and coveted RP. The comparative study will provide boon to regulate the storage water to the posterior areas concerning safety and optimum utilization of water for various uses. Highlights: 24 years daily a peak flood flow data recorded by stepped weir was used. The linear log-regression method is highly suitable for flood frequency analysis. Linear relationship does not exist in the natural event of occurrence of floods and it was proved. For smaller return periods, plotting position method yielded to produce better results besides easy and convenient. For higher return periods, Gumbel's analytical method yielded to produce better results.